Non-formal and Out-of-School Education for Sustainable Development: A Systematic Literature Review - Wittlich, Christian; Wahl, Pia; Schult, Bente (Journal of Geography Education, 2024)
Numerous empirical studies on the implementation of Education for Sustainable Development (ESD) exist for the formal education sector (Singer-Brodowski et al., 2019). In contrast, the highly differentiated non-formal sector and the overlapping field of out-of-school education are insufficiently addressed (Adomßent, 2016; Wals et al., 2017; Wittlich, 2021). Hence, this publication provides an overview of the current state of research. Using a systematic literature review (PRISMA), the relevant publications are examined through content analysis. The evaluation reveals opportunities, challenges, and research desiderata, from which implications for geography education can be derived.
Keywords: non-formal Education for Sustainable Development, out-of-school-ESD, literature review